ESTIMATED CARBON STOCK IN MANGROVE VEGETATION ON TUNDA ISLAND, SERANG REGENCY, BANTEN PROVINCE - Wardono, Suko; Widayanti, Dhiya Artika; Ismail, R. Moh; Rosalina, Dwi; Rizkiah, Riza (Proceedings of The Vocational Seminar on Marine & Inland Fisheries, 2026)
Tunda Island in Serang Regency, Banten Province, hosts a mangrove ecosystem with significant carbon storage potential, yet remains underutilized in climate mitigation efforts. This study aims to estimate the carbon stock of mangrove vegetation, focusing on leaf and branch components using both destructive and non-destructive methods. Samples were collected from six stations using line transect and 10×10 meter plot techniques. The identified mangrove species included Rhizophora apiculata, Rhizophora stylosa, Avicennia marina, Avicennia officinalis, and Bruguiera gymnorrhiza. Results showed estimated biomass ranging from 0.001757 to 0.024657 tons/ha, while carbon stock in leaves and branches ranged from 0.01197–0.01791 tons/ha and 0.02559–0.04184 tons/ha, respectively. Variations in carbon stock were influenced by dominant species, vegetation density, tree diameter (DBH), and environmental factors. The relatively low carbon values suggest that the mangrove ecosystem in Tunda Island is still in a developing phase. This highlights the need for sustainable conservation and rehabilitation efforts. The findings serve as a scientific foundation for coastal ecosystem management and blue carbon strategies in mitigating climate change.